Why is lead dioxide metallic? - Payne, D; Egdell, R; Hao, W; Foord, J; Walsh, A; Watson, G (2005)
The electronic structure of lead dioxide (PbO2) has been studied by high resolution valence band X-ray photoelectron spectroscopy and electron energy loss spectroscopy, supported by band structure calculations carried out within the framework of density functional theory. The metallic nature of PbO2 is shown to arise from occupation of conduction band states above the Fermi level of stoichiometric PbO2, probably arising from oxygen vacancy defects. Strong satellites are observed in core level photoemission spectra at an energy consistent with the plasmon frequency observed in electron energy loss spectra. © 2005 Elsevier B.V. All rights reserved.